No time like the future [compact disc, unabridged] : an optimist considers mortality - Fox, Michael J., 1961- (Macmillan Audio, 2020)
A moving account of resilience, hope, fear and mortality, and how these things resonate in people's lives, by actor and advocate Michael J. Fox.